STRATEGI PENGELOLAAN PIUTANG PERUSAHAAN OTOMOTIF DIMASA PANDEMI COVID 19 DALAM MENJAGA PROFITABILITAS - Asraf Asraf; Mardahleni Mardahleni; Roza Gustika; Ilham Kurniawan (JURNAL ILMIAH EDUNOMIKA, 2022)
The Covid 19 pandemic even though it has shown signs of abating, the impact on the industry remains large and requires a recovery process to return to normal. During the pandemic, various strategies are needed for the industry to maintain the level of profitability or at least be able to survive at a safe level of profitability or even survive the dream until it suffers a loss that is burdensome for the survival of the company. This study will analyze how the receivables strategy can contribute to the profitability of Automotive Industry companies in Indonesia. The analysis was conducted on 14 automotive companies listed on the Indonesia Stock Exchange by testing the effect of receivables turnover on profitability ratios (ROA, ROE and NPM). The results showed that the receivables turnover did not have a significant effect on the profitability ratios. This means that in the case of the automotive industry, the receivables strategy does not show a significant contribution to efforts to maintain the level of profitability in the automotive industry in Indonesia. This finding indicates that the role of financial institutions is still quite dominant in supporting sales and facilitating customer purchases on credit. Keywords: Accounts Receivable Turnover, Return On Assets, Return On Equity, Net Profit Margin